PENGARUH MENGKONSUMSI PISANG AMBON (MUSA PARADISIACA. S) TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI KELURAHAN KUBU MARAPALAM WILAYAH KERJA PUSKESMAS ANDALAS PADANG - Leni Tri Wahyuni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
World Health Organization (WHO), almost 1 million people on 2011 worldwide have hypertension. Hypertension is one of the main causes of premature death worldwide. Proportional Mortality Rate due to hypertension worldwide is 13% or around 7.1 million deaths. In 2020 around 1.56 billion adults will live with hypertension. Non-pharmacological treatment can be used to reduce mortality and incidence of hypertension. One of them is herbal plants that can reduce blood pressure is musa paradisiaca. S. The purpose of this study was to determine the effect of consuming Musa Paradisiaca. S on blood pressure reduction. This type of research uses Quasi Experiment withresearch design one group pretest-posttest conducted in Kubu Marapalam District, Andalas Public Health Center, Padang on July 20-25. The population in the study were 266 people with a sample of 15 people, the sampling technique used was purposive sampling. consists of 1 treatment group by giving musa paradisiaca. S to the treatment group in the morning and evening. The tools used in this study are tensimeter (spynomanometer), stethoscope, scales, and observation sheets. Data analysis using normality test, namely shapiro-wilk test and continued with paired sample T-test. Based on the results obtained there is an effect of consuming ambon bananas to systolic and diastolic blood pressure with systolic values p = 0,000 and diastolic p = 0,000. and ambon banana gives a significant difference to the decrease in systolic and diastolic blood pressure. So it is recommended for hypertensive patients to reduce the use of pharmacological drugs and can be replaced with non-pharmacological drugs, one of which is musa paradisiaca.